Moisturizers for Skin Barrier Repair: A Scoping Review of Transepidermal Water Loss and Stratum Corneum Hydration (2019-2026) - Kanaya Shabrina Maharani; Ghaisani Zata Dini; Novia Putri Ixanty; Zarifa Ramadani Nurulhuda; Azmi Hendina Putra (Lembaga Pengembangan Kinerja Dosen, 2026)
The skin barrier is the outermost protective layer of the skin that plays an important role in maintaining skin hydration and preventing excessive water loss. Damage to the skin barrier can increase transepidermal water loss (TEWL), causing the skin to become dry, sensitive, and prone to irritation. Moisturizers are used to improve skin barrier function by increasing skin hydration and reducing TEWL. This study aimed to conduct a scoping review of moisturizer formulations for skin barrier repair based on transepidermal water loss (TEWL) and stratum corneum hydration parameters. The research method used was a scoping review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines. Literature searches were conducted through Google Scholar, PubMed, ScienceDirect, and Semantic Scholar databases using research articles published between 2019–2026 related to the study topic. A total of 20 articles met the inclusion criteria, consisting of experimental formulation studies and clinical studies. The review results showed that moisturizers are available in various topical dosage forms such as gels, creams, lotions, serums, emulgels, and cleansers with herbal and modern active ingredients such as ceramide, niacinamide, sodium hyaluronate, and Centella asiatica extracellular vesicles (Cica EVs). Gel preparations were the most commonly used formulations because they have a light texture, are comfortable to use, and are easy to apply to the skin. In experimental studies, emulgel containing limpasu fruit extract showed the most optimal physical characteristics based on viscosity and spreadability parameters. Meanwhile, in clinical studies, ceramide-based moisturizers showed the best effectiveness in increasing skin hydration and significantly reducing TEWL. The effectiveness of moisturizers was also influenced by the combination of humectants, emollients, occlusives, and gelling agents in the formulation. Overall, moisturizers have good potential in increasing skin hydration and improving skin barrier function through reducing TEWL and increasing stratum corneum hydration.